Anticorrosive overhead conductor and method of making and production equipment therefor
Patent Information
- Application Number
- CN202611260311.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]基于此,本申请提供了一种防腐架空导线及其制备方法和生产设备,旨在解决传统防腐架空导线线路损耗高、运行温度高、防护寿命较短的问题
[0029]通过在铝合金芯线以及铝单丝层上附着特定组分的石墨烯防腐脂,并在铝合金芯线与铝单丝层之间的间隙中填充上述的石墨烯防腐脂;该石墨烯防腐脂中包括特定含量的导电型石墨烯、导热型石墨烯、防腐型石墨烯、润滑型石墨烯、纳米银粉、氮化硼纳米片、复合锂-钙稠化剂、助剂以及基础油。通过上述石墨烯防腐脂中的各组分复配,能够有效降低架空导线的层间接触电阻,使架空导线具有较低的线路损耗;能够提升导线的散热性能,降低架空导线的运行温度;同时该石墨烯防腐脂还具有较长的防护寿命,能够延长架空导线的使用寿命。
Smart Images

Figure CN122991744A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of conductor technology, and in particular to a corrosion-resistant overhead conductor, its preparation method, and production equipment. Background Technology
[0002] Traditional bare overhead conductors have a core reinforced with an outer layer of stranded aluminum / aluminum alloy wire. Aluminum alloy stranded wire, on the other hand, is an overhead conductor with an aluminum alloy core and an outer layer of stranded hard aluminum wire, combining the high strength of steel-cored aluminum stranded wire with the excellent conductivity of all-aluminum alloy stranded wire. Because both the core and outer aluminum wire are aluminum-based materials, there are no electrochemical corrosion issues, making it widely used in coastal and industrial atmospheric environments.
[0003] Currently, the corrosion protection of overhead conductors relies on the passive protection provided by the natural oxide film (Al2O3) on the aluminum surface. However, under the influence of marine salt spray, acid rain, and industrial pollutants, the oxide film is easily damaged, leading to pitting and crevice corrosion. Corrosion protection performance can usually be improved by coating or impregnating the overhead conductors with anti-corrosion grease, such as petroleum grease, silicone grease, or ordinary lithium-based grease, which coats the interlayer gaps to isolate moisture and provide lubrication.
[0004] However, current overhead conductors coated with anti-corrosion grease still suffer from drawbacks such as high line loss, high operating temperature, and short protection life. Therefore, traditional technologies need further improvement. Summary of the Invention
[0005] Based on this, this application provides a corrosion-resistant overhead conductor, its preparation method and production equipment, aiming to solve the problems of high line loss, high operating temperature and short protection life of traditional corrosion-resistant overhead conductors.
[0006] To address the above problems, the technical solution proposed in this application is as follows:
[0007] According to one aspect of this application, a corrosion-resistant overhead conductor is provided, comprising an aluminum alloy core wire, an aluminum monofilament layer, and graphene anti-corrosion grease.
[0008] The aluminum monofilament layer is stranded on the outside of the aluminum alloy core wire; graphene anti-corrosion grease is attached to the aluminum alloy core wire and the aluminum monofilament layer, and fills the gap between the aluminum alloy core wire and the aluminum monofilament layer.
[0009] The graphene anticorrosive grease comprises the following components by weight percentage: 0.5%~3.5% conductive graphene, 0.5%~2.5% thermally conductive graphene, 1%~3% anticorrosive graphene, 0.2%~1.8% lubricating graphene, 0.2%~1.5% nano silver powder, 0.2%~1.5% boron nitride nanosheets, 10%~18% composite lithium-calcium thickener, 1.2%~2.4% additives, and the balance being base oil.
[0010] In some embodiments, the conductive graphene is a few-layer graphene with 3 to 5 layers and a sheet diameter of 2 μm to 5 μm.
[0011] In some embodiments, the thermally conductive graphene is nitrogen-doped graphene, wherein the nitrogen content in the nitrogen-doped graphene is 8% to 10% by mass, and the sheet diameter of the nitrogen-doped graphene is 5 μm to 10 μm.
[0012] In some embodiments, the corrosion-resistant graphene is silane coupling agent modified graphene, wherein the density of epoxy groups in the silane coupling agent modified graphene is greater than 0.5 mmol / g, and the sheet diameter of the silane coupling agent modified graphene is 1 μm to 3 μm.
[0013] In some embodiments, the lubricating graphene is oleamide-modified graphene with a sheet diameter of 0.5 μm to 2 μm.
[0014] In some embodiments, the particle size of the silver nanoparticles is 30 nm to 70 nm.
[0015] In some embodiments, the boron nitride nanosheets have a diameter of 80 nm to 120 nm.
[0016] In some embodiments, the molar ratio of lithium hydroxide to calcium hydroxide in the raw materials for preparing the composite lithium-calcium thickener is (2~4):1.
[0017] In some embodiments, the base oil comprises polyalphaolefin synthetic hydrocarbon PAO6 and modified silicone oil, wherein the mass ratio of polyalphaolefin synthetic hydrocarbon PAO6 to modified silicone oil is (1~2):1.
[0018] In some embodiments, the additives include one or more of corrosion inhibitors and extreme pressure anti-wear agents; when the additives include corrosion inhibitors, the mass percentage of corrosion inhibitors in the graphene anticorrosive grease is 1% to 1.4%; when the additives include extreme pressure anti-wear agents, the mass percentage of extreme pressure anti-wear agents in the graphene anticorrosive grease is 1% to 1.4%.
[0019] In some embodiments, the aluminum alloy core wire includes a first aluminum alloy monofilament and multiple second aluminum alloy monofilaments, with the multiple second aluminum alloy monofilaments twisted around the outside of the first aluminum alloy monofilament.
[0020] In some embodiments, the aluminum monofilament layer includes a first aluminum monofilament layer and a second aluminum monofilament layer, wherein the first aluminum monofilament layer is stranded on the outside of the aluminum alloy core wire, and the second aluminum monofilament layer is stranded on the outside of the first aluminum monofilament layer.
[0021] According to a second aspect of this application, a method for preparing an anti-corrosion overhead conductor according to the first aspect of this application is provided, comprising the following steps: coating multiple aluminum monofilaments with graphene anti-corrosion grease, and twisting the aluminum monofilaments coated with graphene anti-corrosion grease to the outside of an aluminum alloy core wire to form an aluminum monofilament layer.
[0022] In some embodiments, the method for preparing the aluminum alloy core wire includes the following steps: coating a first aluminum alloy monofilament and a second aluminum alloy monofilament with graphene anti-corrosion grease; and twisting multiple second aluminum alloy monofilaments to the outside of the first aluminum alloy monofilament.
[0023] In some embodiments, the aluminum monofilament coated with graphene anti-corrosion grease is twisted to the outside of the aluminum alloy core wire, including the following steps: twisting multiple aluminum monofilaments coated with graphene anti-corrosion grease to the outside of the aluminum alloy core wire to form a first aluminum monofilament layer; and twisting multiple aluminum monofilaments coated with graphene anti-corrosion grease to the outside of the first aluminum monofilament layer.
[0024] According to a third aspect of this application, a production apparatus for the anti-corrosion overhead conductor of the first aspect of this application or a production apparatus for the preparation method of the anti-corrosion overhead conductor of the second aspect of this application is provided, comprising an anti-corrosion grease coating device, the anti-corrosion grease coating device comprising:
[0025] The outer casing has an inner cavity, and the outer casing is provided with a first outer casing oil inlet hole and a second outer casing oil inlet hole that communicate with the inner cavity.
[0026] A coating mold is placed in the inner cavity of the outer shell. The coating mold includes a first half mold and a second half mold. When the first half mold and the second half mold are combined, they form a wire through hole. The first half mold and the second half mold are respectively provided with a first half mold oil inlet hole and a second half mold oil inlet hole. The first half mold oil inlet hole is connected to the first outer shell oil inlet hole, and the second half mold oil inlet hole is connected to the second outer shell oil inlet hole.
[0027] In some embodiments, the anti-corrosion grease coating device further includes a first flow limiting sensor and a second flow limiting sensor, which are respectively disposed on the inner sidewalls of the first housing oil inlet and the second housing oil inlet.
[0028] Compared with traditional technologies, this application has at least the following beneficial effects:
[0029] A graphene anti-corrosion grease with specific components is applied to aluminum alloy core wires and aluminum monofilament layers, and the gap between the aluminum alloy core wires and aluminum monofilament layers is filled with the aforementioned graphene anti-corrosion grease. This graphene anti-corrosion grease includes specific amounts of conductive graphene, thermally conductive graphene, anti-corrosion graphene, lubricating graphene, nano-silver powder, boron nitride nanosheets, composite lithium-calcium thickener, additives, and base oil. Through the compounding of the various components in the above-mentioned graphene anti-corrosion grease, the interlayer contact resistance of overhead conductors can be effectively reduced, resulting in lower line losses; the heat dissipation performance of the conductors can be improved, reducing the operating temperature of the overhead conductors; and the graphene anti-corrosion grease also has a long protective life, extending the service life of the overhead conductors. Attached Figure Description
[0030] To better describe and illustrate embodiments and / or examples of this application, reference may be made to one or more accompanying drawings. Additional details or examples used to describe the drawings should not be considered as limiting the scope of any of the disclosed applications, the currently described embodiments and / or examples, or the best mode of these applications as currently understood.
[0031] Figure 1 This is a schematic diagram of the structure of an anti-corrosion overhead conductor according to one embodiment of this application.
[0032] Figure 2 This is a schematic diagram of the structure of the anti-corrosion grease coating device according to one embodiment of this application during use.
[0033] Figure 3 This is a schematic diagram of the end of an anti-corrosion grease coating device according to an embodiment of this application.
[0034] Figure 4 This is a schematic diagram of the coating mold in an anti-corrosion grease coating apparatus according to an embodiment of this application.
[0035] Figure 5 This is a schematic diagram of the end of the coating mold in an anti-corrosion grease coating apparatus according to an embodiment of this application.
[0036] Explanation of reference numerals in the attached figures:
[0037] 10. Corrosion-resistant overhead conductor; 11. Aluminum alloy core wire; 12. Aluminum monofilament layer; 13. Graphene anti-corrosion grease; 20. Anti-corrosion grease coating device; 21. Housing; 22. Coating mold; 23. First current limiting sensor; 24. Second current limiting sensor; 111. First aluminum alloy monofilament; 112. Second aluminum alloy monofilament; 121. First aluminum monofilament layer; 122. Second aluminum monofilament layer; 211. First housing oil inlet; 212. Second housing oil inlet; 221. First half mold; 222. Second half mold; 223. Wire through hole; 2211. First half mold oil inlet; 2221. Second half mold oil inlet. Detailed Implementation
[0038] To make the above-mentioned objectives, features, and advantages of this application more apparent and understandable, a detailed description of specific embodiments of this application is provided below. Many specific details are set forth in the following description to provide a thorough understanding of this application. However, this application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of this application. Therefore, this application is not limited to the specific embodiments disclosed below.
[0039] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60~120 and 80~110 are listed for a specific parameter, it is also expected that ranges of 60~110 and 80~120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1~3, 1~4, 1~5, 2~3, 2~4, and 2~5. In this application, unless otherwise stated, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0~5" indicates that all real numbers between "0~5" have been listed in this article; "0~5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. Unless otherwise specifically stated, all raw materials, reagents, instruments, and equipment used in this application are commercially available or can be prepared by existing methods.
[0041] Traditional overhead conductors coated with anti-corrosion grease suffer from drawbacks such as high line loss, high operating temperature, and short protective life. Firstly, both hard aluminum wire and aluminum alloy core wire have an oxide film (Al2O3) on their surface. Traditional anti-corrosion grease, acting as an insulating medium, cannot effectively conduct interlayer current, leading to significant additional losses. Furthermore, as operating time increases, the oxide film thickens, further increasing resistance, creating a vicious cycle of "heating-oxidation-increased resistance," resulting in high line loss. Secondly, the aluminum alloy core wire bears the main mechanical load. Traditional anti-corrosion grease has a thermal conductivity of only 0.1~0.2 W / m·K, resulting in high interlayer thermal resistance. Heat cannot be effectively dissipated from the core wire, and high temperatures accelerate core wire creep, leading to increased sag and reduced strength. Thirdly, traditional anti-corrosion greases, such as petroleum grease and silicone grease, adhere to the aluminum surface only through van der Waals forces. Under ultraviolet light, ozone, and high temperatures, they are prone to cracking, powdering, and loss, making them unsuitable for the large temperature differences between northern and southern my country, resulting in a short actual protective life.
[0042] See Figure 1 One embodiment of this application provides a corrosion-resistant overhead conductor 10, which includes an aluminum alloy core wire 11, an aluminum monofilament layer 12, and a graphene anti-corrosion grease 13; the aluminum monofilament layer 12 is stranded on the outside of the aluminum alloy core wire 11; the graphene anti-corrosion grease 13 is attached to the aluminum alloy core wire 11 and the aluminum monofilament layer 12, and fills the gap between the aluminum alloy core wire 11 and the aluminum monofilament layer 12; the graphene anti-corrosion grease 13 includes the following components by mass percentage: 0.5%~3.5% conductive graphene, 0.5%~2.5% thermally conductive graphene, 1%~3% corrosion-resistant graphene, 0.2%~1.8% lubricating graphene, 0.2%~1.5% nano silver powder, 0.2%~1.5% boron nitride nanosheets, 10%~18% composite lithium-calcium thickener, 1.2%~2.4% additives, and the balance being base oil.
[0043] The corrosion-resistant overhead conductor 10 described above in this application has a graphene anti-corrosion grease 13 of a specific composition attached to the aluminum alloy core wire 11 and the aluminum monofilament layer 12, and the graphene anti-corrosion grease 13 is filled in the gap between the aluminum alloy core wire 11 and the aluminum monofilament layer 12. The conductive graphene in the graphene anti-corrosion grease 13 can form a three-dimensional conductive network, reducing the interlayer contact resistance of the overhead conductor. The thermally conductive graphene has a large in-plane thermal conductivity, which can quickly conduct heat and help reduce the operating temperature of the conductor. The corrosion-resistant graphene can form a chemical bond with the aluminum surface, playing a long-term anti-corrosion role and extending the protection life of the conductor. Lubricating graphene acts as an interlayer lubricant, reducing the interlayer friction coefficient; nano-silver powder fills the gaps between graphene layers, enhancing conductivity; boron nitride nanosheets disrupt the orientation of graphene layers, forming a three-dimensional thermally conductive network, improving the isotropic thermal conductivity of the preservative grease, and synergistically enhancing heat dissipation performance; the composite lithium-calcium thickener gives the preservative grease a high dropping point, making it less prone to melting and liquefaction at high temperatures, and also gives the preservative grease good mechanical stability; at the same time, the composite lithium-calcium thickener acts as a carrier, firmly locking in the base oil and uniformly dispersing graphene, nano-silver powder, and boron nitride nanosheets, ensuring uniform distribution of each component.
[0044] By using the graphene anti-corrosion grease 13 described above, the interlayer contact resistance of overhead conductors can be reduced, resulting in lower line losses; the heat dissipation performance of the conductors can be improved, reducing the operating temperature of the overhead conductors; at the same time, the graphene anti-corrosion grease 13 also has a long protective life, which can extend the service life of the overhead conductors.
[0045] It should be noted that the dropping point refers to the temperature at which the preservative softens, thins, and finally drips after being heated, at which point the first drop of preservative falls.
[0046] In some embodiments, the conductive graphene is few-layer graphene with 3 to 5 layers and a sheet diameter of 2 μm to 5 μm. Here, few-layer graphene refers to naturally stacked graphene that has not been oxidized or exfoliated with strong acid. Using the aforementioned few-layer graphene as the conductive graphene is beneficial for constructing a three-dimensional conductive network and reducing interlayer contact resistance. It is understood that the sheet diameter of the few-layer graphene can be 2 μm, 2.2 μm, 2.5 μm, 2.8 μm, 3 μm, 3.2 μm, 3.5 μm, 3.8 μm, 4 μm, 4.2 μm, 4.5 μm, 4.8 μm, 5 μm, or any value within the range formed by any two of the above values.
[0047] In some embodiments, the thermally conductive graphene is nitrogen-doped graphene, wherein the nitrogen content in the nitrogen-doped graphene is 8% to 10% by mass, and the sheet diameter of the nitrogen-doped graphene is 5 μm to 10 μm. Using the above-mentioned nitrogen-doped graphene as the thermally conductive graphene, its in-plane thermal conductivity can reach over 1500 W / m·K, which is beneficial for rapid heat conduction, effectively improving the heat dissipation performance of the wire and reducing the operating temperature. It is understood that the nitrogen content in the nitrogen-doped graphene can be 8%, 8.2%, 8.5%, 8.8%, 9%, 9.2%, 9.5%, 9.8%, 10%, or any value within the range formed by any two of the above values; the sheet diameter of the nitrogen-doped graphene can be 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, or any value within the range formed by any two of the above values.
[0048] In some embodiments, the corrosion-resistant graphene is silane coupling agent-modified graphene, wherein the density of epoxy groups in the silane coupling agent-modified graphene is greater than 0.5 mmol / g, and the sheet diameter of the silane coupling agent-modified graphene is 1 μm to 3 μm. Using the above-mentioned silane coupling agent-modified graphene as the corrosion-resistant graphene allows it to form good chemical bonds with the aluminum surface, prolonging the protective effect of the anti-corrosion grease. The silane coupling agent can be, for example, KH-560. It is understood that the sheet diameter of the silane coupling agent-modified graphene can be 1 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2 μm, 2.2 μm, 2.5 μm, 2.8 μm, 3 μm, or any value within the range formed by any two of the above values.
[0049] In some embodiments, the lubricating graphene is oleamide-modified graphene with a sheet diameter of 0.5 μm to 2 μm. Using the aforementioned oleamide-modified graphene as the lubricating graphene can provide excellent interlayer superlubrication and reduce the interlayer friction coefficient. It is understood that the sheet diameter of the oleamide-modified graphene can be 0.5 μm, 0.8 μm, 1 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2 μm, or any value within the range formed by any two of the above values.
[0050] In some embodiments, the particle size of the silver nanoparticles is 30nm to 70nm. Using silver nanoparticles with this particle size is beneficial for better filling the gaps between various graphene particles, further enhancing the conductivity of the anti-corrosion grease. It is understood that the particle size of the silver nanoparticles can be 30nm, 32nm, 35nm, 38nm, 40nm, 42nm, 45nm, 48nm, 50nm, 52nm, 55nm, 58nm, 60nm, 62nm, 65nm, 68nm, 70nm, or any value within the range formed by any two of the above values.
[0051] In some embodiments, the boron nitride nanosheets have a diameter of 80 nm to 120 nm. It is understood that the diameter of the boron nitride nanosheets can be 80 nm, 82 nm, 85 nm, 88 nm, 90 nm, 92 nm, 95 nm, 98 nm, 100 nm, 102 nm, 105 nm, 108 nm, 110 nm, 112 nm, 115 nm, 118 nm, 120 nm, or any value within the range formed by any two of the above values.
[0052] In some embodiments, the molar ratio of lithium hydroxide to calcium hydroxide in the raw materials for preparing the composite lithium-calcium thickener is (2~4):1. Further optionally, the molar ratio of lithium hydroxide to calcium hydroxide is 3:1. The composite lithium-calcium thickener is a composite lithium-calcium salt generated by the co-saponification reaction of fatty acids, lithium hydroxide, and calcium hydroxide. Commercially available products can be used as the composite lithium-calcium thickener.
[0053] In some embodiments, the base oil comprises polyalphaolefin (PAO6) and modified silicone oil, wherein the mass ratio of PAO6 to modified silicone oil is (1-2):1. More optionally, the mass ratio of PAO6 to modified silicone oil is 1.5:1. For example, PAO6 accounts for 60% and modified silicone oil accounts for 40%. This base oil has a wide temperature range. The modified silicone oil can be, but is not limited to, methylphenyl modified silicone oil, long-chain alkyl modified silicone oil, fluorinated modified silicone oil, etc.
[0054] In some embodiments, the additives include one or more of corrosion inhibitors and extreme pressure anti-wear agents; when the additives include corrosion inhibitors, the mass percentage of the corrosion inhibitor in the graphene anticorrosive grease is 1% to 1.4%; when the additives include extreme pressure anti-wear agents, the mass percentage of the extreme pressure anti-wear agent in the graphene anticorrosive grease is 1% to 1.4%. The corrosion inhibitor may be a compound of benzotriazole and cerium nitrate, and the extreme pressure anti-wear agent may be a compound of phosphate ester amine salt and borate ester. The corrosion inhibitor can synergistically work with graphene to provide electrochemical protection; the extreme pressure anti-wear agent can improve the resistance of the conductor to fretting wear.
[0055] In some specific examples, the additives include a corrosion inhibitor comprising 1.2% by mass of graphene anticorrosive grease 13 and an extreme pressure anti-wear agent comprising 1.2% by mass.
[0056] In some embodiments, the aluminum alloy core wire 11 includes a first aluminum alloy monofilament 111 and multiple second aluminum alloy monofilaments 112, with the multiple second aluminum alloy monofilaments 112 twisted around the outside of the first aluminum alloy monofilament 111. That is, the aluminum alloy core wire 11 is a core wire formed by twisting one first aluminum alloy monofilament 111 with multiple second aluminum alloy monofilaments 112. The multiple second aluminum alloy monofilaments 112 are located outside the first aluminum alloy monofilament 111. In some specific examples, the number of second aluminum alloy monofilaments 112 is six.
[0057] In some embodiments, the aluminum monofilament layer 12 includes a first aluminum monofilament layer 121 and a second aluminum monofilament layer 122. The first aluminum monofilament layer 121 is stranded on the outside of the aluminum alloy core wire 11, and the second aluminum monofilament layer 122 is stranded on the outside of the first aluminum monofilament layer 121. Exemplarily, the aluminum monofilament layer 12 is divided into two layers: the inner first aluminum monofilament layer 121 is stranded on the outside of the aluminum alloy core wire 11, and the outer second aluminum monofilament layer 122 is stranded on the outside of the first aluminum monofilament layer 121. In some specific examples, the first aluminum monofilament layer 121 contains 12 aluminum monofilaments, and the second aluminum monofilament layer 122 contains 18 aluminum monofilaments.
[0058] One embodiment of this application provides a method for preparing the corrosion-resistant overhead conductor 10 described above, comprising the following steps: coating multiple aluminum monofilaments with graphene anti-corrosion grease 13, twisting the aluminum monofilaments coated with graphene anti-corrosion grease 13 to the outside of the aluminum alloy core wire 11, and naturally cooling to form an aluminum monofilament layer 12.
[0059] Understandably, after the aluminum monofilament coated with graphene anti-corrosion grease 13 is twisted to the outside of the aluminum alloy core wire 11, the graphene anti-corrosion grease 13 will adhere to the aluminum monofilament and the aluminum alloy core wire 11, and fill the gap between the aluminum alloy core wire 11 and the aluminum monofilament layer 12.
[0060] Furthermore, the preparation method of the aluminum alloy core wire 11 includes the following steps: coating the first aluminum alloy monofilament 111 and the second aluminum alloy monofilament 112 with graphene anti-corrosion grease 13; and twisting multiple second aluminum alloy monofilaments 112 to the outside of the first aluminum alloy monofilament 111.
[0061] Furthermore, the aluminum monofilament coated with graphene anti-corrosion grease 13 is twisted to the outside of the aluminum alloy core wire 11, including the following steps: twisting multiple aluminum monofilaments coated with graphene anti-corrosion grease 13 to the outside of the aluminum alloy core wire 11 to form a first aluminum monofilament layer 121; twisting multiple aluminum monofilaments coated with graphene anti-corrosion grease 13 to the outside of the first aluminum monofilament layer 121 to form a second aluminum monofilament layer 122.
[0062] In some specific examples, the corrosion-resistant overhead conductor 10 is prepared by the following steps:
[0063] (1) First layer of twisting
[0064] A 3.0mm diameter aluminum alloy monofilament is coated with graphene anti-corrosion grease using a specialized coating device (3.2mm inner diameter, 10cm length, split upper and lower sections). Oil inlet parameters: pressure at both upper and lower inlets is 0.3MPa, oil temperature is 85℃. A graphene anti-corrosion grease layer is uniformly coated onto the surface of the aluminum alloy monofilament. Six 3.0mm diameter aluminum alloy monofilaments are then twisted around the aluminum alloy monofilament core wire at a tension of 150N~200N. The twisting pressure ensures the anti-corrosion grease fully fills the interlayer gaps, achieving a sealing and anti-corrosion effect, resulting in an aluminum alloy core wire filled and coated with graphene anti-corrosion grease.
[0065] (2) Second layer twisting
[0066] The aluminum monofilament is passed through a coating device (with an inner diameter of Φ9.0mm); the oil inlet parameters are: pressure 0.35MPa, oil temperature 90℃; a graphene anti-corrosion grease layer is uniformly coated on the surface of the aluminum monofilament; with the aluminum alloy core wire as the center, 12 Φ3.0mm aluminum monofilaments are twisted around the outside of the aluminum alloy core wire with a twisting tension of 250N~300N to obtain an aluminum alloy core wire with a first layer of aluminum monofilaments.
[0067] (3) Third layer twisting
[0068] Aluminum monofilaments are passed through a coating device (inner hole Φ15.0mm); oil inlet parameters: pressure 0.4MPa, oil temperature 95℃; a graphene anti-corrosion grease layer is uniformly coated on the surface of the aluminum monofilaments; with the aluminum alloy core wire with the first aluminum monofilament layer as the center, 18 Φ3.0mm aluminum monofilaments are twisted together on the outside of the first aluminum monofilament layer, with a twisting tension of 350N~400N, to obtain an unshaped overhead conductor.
[0069] (4) Cooling, shaping and winding
[0070] The conductors are allowed to cool naturally to room temperature to avoid rapid cooling that could cause the graphene anti-corrosion grease to shrink and crack. The winding tension is controlled at 500N~800N to ensure that the wiring is tight, neat, and free of loose strands, thus obtaining anti-corrosion overhead conductors.
[0071] In some embodiments, the preparation process of the aluminum alloy monofilament in the aluminum alloy core wire is as follows: An Al-Mg-Si series aluminum alloy rod (9.5mm in diameter) is selected as the core material; a continuous wire drawing machine is used for multi-pass drawing, with a die compression rate of 18%~23% per pass and a constant speed wheel linear speed of 8m / s~12m / s; the die path is: 9.5mm→7.5mm→6.0mm→4.8mm→3.8mm→3.0mm (6 passes in total). After drawing, intermediate annealing is performed: holding at 380℃ for 2 hours to eliminate work hardening; the finished monofilament has a diameter of 3.0mm, a tensile strength ≥295MPa, and an elongation ≥4%; then, aging treatment is performed: holding at 145℃ for 8 hours, the strength recovers to 315MPa, obtaining a high-strength aluminum alloy monofilament.
[0072] In some embodiments, the preparation process of the aluminum monofilament is as follows: a high-conductivity L3 aluminum rod is selected as the raw material for the aluminum monofilament, with a rod diameter of 9.5 mm; it is drawn using a continuous wire drawing machine, with a single-pass die compression rate of 22%~27% and a constant-speed wheel linear speed of 9 m / s~16 m / s; the die path is: 9.5 mm → 7.8 mm → 6.3 mm → 5.1 mm → 4.1 mm → 3.3 mm → 2.7 mm, for a total of 6 passes; the intermediate annealing temperature is 320℃, and the holding time is 2 hours to eliminate work hardening and restore conductivity; the finished single wire has a diameter of 3.0 mm, a conductivity ≥62.5% IACS, and a tensile strength ≥165 MPa.
[0073] In some specific examples, the preparation method of graphene preservatives is as follows:
[0074] (1) Preparation of conductive graphene (c-Gr)
[0075] Natural graphite powder and N-methylpyrrolidone (NMP) were mixed at a mass ratio of 1:50 and ultrasonically treated at 500W for 4 hours at 25℃. Then, the mixture was centrifuged at 3000rpm for 10 minutes, and the upper dispersion was collected and vacuum dried at 80℃ for 12 hours to obtain few-layer conductive graphene.
[0076] (2) Preparation of thermally conductive graphene (t-Gr)
[0077] Graphene oxide was dispersed in deionized water to prepare a 5 mg / mL dispersion. Urea was added at a mass ratio of graphene oxide to urea of 1:10, and the mixture was sonicated for 30 min. The mixture was then transferred to a tube furnace and reacted at 800 °C in an NH3 atmosphere for 2 h. After natural cooling, nitrogen-doped thermally conductive graphene was obtained.
[0078] (3) Preparation of corrosion-resistant graphene (a-Gr)
[0079] Graphene oxide was dispersed in anhydrous toluene to prepare a 5 mg / mL dispersion, and sonicated for 30 min. Coupling agent was added at a mass ratio of graphene oxide to KH-560 silane coupling agent of 1:0.5, and the mixture was refluxed at 110 °C for 4 h under nitrogen protection. Then, reducing agent was added at a mass ratio of graphene oxide to 80% hydrazine hydrate of 1:2, and the mixture was reduced at 85 °C for 2 h. After centrifugation and washing three times each with ethanol and water, the mixture was vacuum dried at 60 °C for 12 h to obtain corrosion-resistant graphene.
[0080] (4) Preparation of lubricated graphene (l-Gr)
[0081] Expanded graphite and oleamide were mixed at a mass ratio of 1:5, and then ball-milled for 6 hours using a planetary ball mill at a speed of 400 rpm and a ball-to-material ratio of 10:1. Excess oleamide was removed by washing with petroleum ether and dried at 60°C to obtain oleamide-modified lubricating graphene.
[0082] (5) Preparation of basal fat bodies
[0083] A base oil was prepared by compounding PAO6 synthetic oil (60%) and modified silicone oil (40%) as a base oil, adding a composite lithium-calcium thickener, adding the remaining base oil, and homogenizing.
[0084] (6) Mixing and dispersing
[0085] The base liposome was cooled to 130℃, and thermally conductive graphene and boron nitride nanosheets were added. The mixture was then dispersed at high shear at 3000 rpm for 30 min. The temperature was then lowered to 110℃, and conductive graphene and nano-silver powder were added. The mixture was then dispersed at high shear for 20 min. The temperature was then lowered to 90℃, and corrosion-resistant graphene and corrosion inhibitor were added. The mixture was then dispersed at high shear for 20 min. Finally, lubricating graphene and extreme pressure anti-wear agent were added. The mixture was then dispersed at high shear for 10 min to complete the multi-stage dispersion.
[0086] (7) Grinding and degassing
[0087] The graphene preservative was produced by grinding the material in stages using a three-roll mill, with the roller gap adjusted sequentially to 10μm→5μm→2μm, and each stage was ground twice. The fineness was checked with a scraper fineness gauge to ensure that the fineness was ≤10μm (99% pass rate). The material was then degassed under vacuum for 30 minutes at -0.09MPa and 60℃, and packaged under nitrogen protection to obtain the finished graphene preservative.
[0088] See Figure 2 , Figure 3 , Figure 4 and Figure 5According to one embodiment of this application, a production equipment for the anti-corrosion overhead conductor 10 described above or a production equipment for the preparation method of the anti-corrosion overhead conductor 10 described above is provided. The production equipment includes an anti-corrosion grease coating device 20, which includes a housing 21 and a coating mold 22. The housing 21 has an inner cavity and a first housing oil inlet hole 211 and a second housing oil inlet hole 212. The coating mold 22 is placed in the inner cavity of the housing 21 and includes a first half mold 221 and a second half mold 222. When the first half mold 221 and the second half mold 222 are combined, a conductor through hole 223 is formed. The first half mold 221 and the second half mold 222 respectively have a first half mold oil inlet hole 2211 and a second half mold oil inlet hole 2221. The first half mold oil inlet hole 2211 communicates with the first housing oil inlet hole 211, and the second half mold oil inlet hole 2221 communicates with the second housing oil inlet hole 212.
[0089] The aforementioned anti-corrosion grease coating device 20 comprises a coating mold 22 consisting of a first half-mold 221 and a second half-mold 222, which is installed inside the housing 21. When combined, the first half-mold 221 and the second half-mold 222 form a wire through-hole 223 for the wire to pass through. In use, the wire to be coated with anti-corrosion grease is passed through the wire through-hole 223, with the diameter of the through-hole 223 slightly larger than the diameter of the wire. Graphene anti-corrosion grease 13 is injected into the wire through-hole 223 through the oil inlet hole 2211 of the first half-mold and / or the oil inlet hole 2221 of the second half-mold. By rotating the wire, the anti-corrosion grease can be evenly coated on the surface of the wire.
[0090] Furthermore, since the coating mold 22 and the outer shell 21 are separable, and the first half mold 221 and the second half mold 222 are separable, the coating device can select coating molds with different wire through hole 223 diameters according to the diameter of different wires, which has good flexibility of use.
[0091] See Figure 3 In some embodiments, the anti-corrosion grease coating device 20 further includes a first flow-limiting sensor 23 and a second flow-limiting sensor 24, which are respectively disposed on the inner sidewalls of the first housing oil inlet 211 and the second housing oil inlet 212. Thus, the status of the graphene anti-corrosion grease 13 in the anti-corrosion grease coating device 20 can be detected by the first flow-limiting sensor 23 and the second flow-limiting sensor 24. When the flow rate of the graphene anti-corrosion grease 13 is too high, resulting in uneven oil inflow, or when excessive oil remains in the holes due to special reasons, oil inflow is stopped. Oil inflow is resumed only after the anti-corrosion grease is properly or evenly coated. This helps to further improve the uniformity of anti-corrosion grease coating and reduce grease waste.
[0092] The present application will be further described below with reference to specific embodiments and comparative examples, but should not be construed as limiting the scope of protection of the present application.
[0093] Example 1:
[0094] (1) Preparation of conductive graphene
[0095] Natural graphite powder and N-methylpyrrolidone were mixed at a mass ratio of 1:50 and ultrasonically treated at 500W for 4 hours at 25℃. Then, the mixture was centrifuged at 3000rpm for 10 minutes, and the upper dispersion was collected and vacuum dried at 80℃ for 12 hours to obtain few-layer conductive graphene.
[0096] (2) Preparation of thermally conductive graphene
[0097] Graphene oxide was dispersed in deionized water to prepare a 5 mg / mL dispersion. Urea was added at a mass ratio of graphene oxide to urea of 1:10, and the mixture was sonicated for 30 min. The mixture was then transferred to a tube furnace and reacted at 800 °C in an NH3 atmosphere for 2 h. After natural cooling, nitrogen-doped thermally conductive graphene was obtained.
[0098] (3) Preparation of corrosion-resistant graphene
[0099] Graphene oxide was dispersed in anhydrous toluene to prepare a 5 mg / mL dispersion, and sonicated for 30 min. Coupling agent was added at a mass ratio of graphene oxide to KH-560 silane coupling agent of 1:0.5, and the mixture was refluxed at 110 °C for 4 h under nitrogen protection. Then, reducing agent was added at a mass ratio of graphene oxide to 80% hydrazine hydrate of 1:2, and the mixture was reduced at 85 °C for 2 h. After centrifugation and washing three times each with ethanol and water, the mixture was vacuum dried at 60 °C for 12 h to obtain corrosion-resistant graphene.
[0100] (4) Preparation of lubricated graphene
[0101] Expanded graphite and oleamide were mixed at a mass ratio of 1:5, and then ball-milled for 6 hours using a planetary ball mill at a speed of 400 rpm and a ball-to-material ratio of 10:1. Excess oleamide was removed by washing with petroleum ether and dried at 60°C to obtain oleamide-modified lubricating graphene.
[0102] (5) Preparation of basal fat bodies
[0103] A base oil was prepared by compounding PAO6 synthetic oil (60%) and modified silicone oil (40%) as a base oil, adding a composite lithium-calcium thickener, adding the remaining base oil, and homogenizing.
[0104] (6) Mixing and dispersing
[0105] The base liposome was cooled to 130℃, and thermally conductive graphene and boron nitride nanosheets were added. The mixture was then dispersed at high shear at 3000 rpm for 30 min. The temperature was then lowered to 110℃, and conductive graphene and nano-silver powder were added. The mixture was then dispersed at high shear for 20 min. The temperature was then lowered to 90℃, and corrosion-resistant graphene and corrosion inhibitor were added. The mixture was then dispersed at high shear for 20 min. Finally, lubricating graphene and extreme pressure anti-wear agent were added. The mixture was then dispersed at high shear for 10 min to complete the multi-stage dispersion.
[0106] (7) Grinding and degassing
[0107] The graphene preservative was produced by grinding the material in stages using a three-roll mill, with the roller gap adjusted sequentially to 10μm→5μm→2μm, and each stage was ground twice. The fineness was checked with a scraper fineness gauge to ensure that the fineness was ≤10μm (99% pass rate). The material was then degassed under vacuum for 30 minutes at -0.09MPa and 60℃, and packaged under nitrogen protection to obtain the finished graphene preservative.
[0108] The mass ratio of each component in the graphene anticorrosive grease is as follows: conductive graphene 2%, thermally conductive graphene 1.5%, anticorrosive graphene 2%, lubricating graphene 1%, nano silver powder 0.8%, boron nitride nanosheets 0.8%, composite lithium-calcium thickener 14%, corrosion inhibitor 1.2%, extreme pressure anti-wear agent 1.2%, and the balance is base oil.
[0109] (8) First layer of twisting
[0110] A 3.0mm diameter aluminum alloy monofilament is coated with graphene anti-corrosion grease through a wire perforation (3.2mm inner hole, 10cm length, split type) of a coating device. The oil inlet parameters are: 0.3MPa pressure in both the first and second half-die oil inlet holes, and 85℃ oil temperature. A graphene anti-corrosion grease layer is uniformly coated on the surface of the aluminum alloy monofilament. Six 3.0mm diameter aluminum alloy monofilaments are twisted around the aluminum alloy monofilament core wire with a twisting tension of 200N to obtain an aluminum alloy core wire filled and coated with graphene anti-corrosion grease.
[0111] (9) Second layer twisting
[0112] Aluminum monofilaments are pierced through a wire hole (inner hole Φ9.0mm) in a coating device; oil inlet parameters: pressure 0.35MPa, oil temperature 90℃; a graphene anti-corrosion grease layer is uniformly coated on the surface of the aluminum monofilaments; 12 Φ3.0mm aluminum monofilaments are twisted around the aluminum alloy core wire with the above-mentioned aluminum alloy core wire as the center, and the twisting tension is 300N, thus obtaining an aluminum alloy core wire with the first aluminum monofilament layer twisted together.
[0113] (10) Third layer twisting
[0114] Aluminum monofilaments are pierced through a wire hole (inner hole Φ15.0mm) in a coating device; oil inlet parameters: pressure 0.4MPa, oil temperature 95℃; a graphene anti-corrosion grease layer is uniformly coated on the surface of the aluminum monofilaments; with the aluminum alloy core wire with the first aluminum monofilament layer as the center, 18 Φ3.0mm aluminum monofilaments are twisted together on the outside of the first aluminum monofilament layer with a twisting tension of 400N to obtain an unshaped overhead conductor.
[0115] (11) Cooling, shaping and winding
[0116] The conductor is allowed to cool naturally to room temperature, and the winding tension is controlled at 600N to obtain a corrosion-resistant overhead conductor.
[0117] Example 2:
[0118] This embodiment is basically the same as embodiment 1, except that the mass ratio of each component of the graphene anticorrosive grease in step (7) is as follows: 1% conductive graphene, 2.5% thermally conductive graphene, 2.5% anticorrosive graphene, 0.8% lubricating graphene, 1% nano silver powder, 1% boron nitride nanosheets, 12% composite lithium-calcium thickener, 1% corrosion inhibitor, 1.4% extreme pressure anti-wear agent, and the remainder is base oil.
[0119] Example 3:
[0120] This embodiment is basically the same as embodiment 1, except that the mass ratio of each component of the graphene anticorrosive grease in step (7) is as follows: 3% conductive graphene, 1% thermally conductive graphene, 2% anticorrosive graphene, 1.8% lubricating graphene, 0.8% nano silver powder, 1.2% boron nitride nanosheets, 10% composite lithium-calcium thickener, 1.2% corrosion inhibitor, 1.2% extreme pressure anti-wear agent, and the remainder is base oil.
[0121] Comparative Example 1:
[0122] This comparative example is essentially the same as Example 1, except that a commercially available ordinary lithium-based grease is used instead of the graphene anti-corrosion grease of this application, and the coating process is different. The formula (by weight percentage) of the commercially available ordinary lithium-based grease is: 75% mineral oil, 12% lithium-based thickener, 3% rust inhibitor (barium petroleum sulfonate), 2% extreme pressure anti-wear agent, 1% antioxidant, and 7% conventional lithium-based grease additives, including structural stabilizers, metal passivators, and tackifiers. The grease contains no graphene, nano-silver powder, boron nitride, or other functional fillers. The coating process uses a traditional dip-coating method, immersing the stranded wires entirely in the anti-corrosion grease bath for coating, allowing it to drip naturally.
[0123] Comparative Example 2:
[0124] This comparative example is essentially the same as Example 1, except that a single graphene anti-corrosion grease is used instead of the graphene anti-corrosion grease of this application. The formulation (by weight percentage) of the single graphene anti-corrosion grease is as follows: 6% few-layer graphene (single type), 60% base oil, 14% lithium-based thickener, 2% rust inhibitor, and 18% conventional lithium-based lubricating grease additives, including structural stabilizers, metal passivators, and tackifiers. The anti-corrosion grease does not differentiate between thermally conductive graphene, anti-corrosion graphene, and lubricating graphene, nor does it contain nano-silver powder or boron nitride.
[0125] The test methods are shown in Table 1 below:
[0126] Table 1
[0127]
[0128] The main parameters and performance data of the overhead conductors in the above embodiments and comparative examples are shown in Table 2.
[0129] Table 2
[0130]
[0131] As shown in Table 2, the anti-corrosion overhead conductors of the various embodiments of this application have low DC resistance, low operating temperature, low core wire temperature and low interlayer temperature, resulting in low line loss. Furthermore, the anti-corrosion overhead conductors have a long salt spray test life, low self-corrosion current density and low anti-corrosion grease loss rate, thus exhibiting a long protective life.
[0132] In Comparative Example 1, commercially available ordinary lithium-based grease was used instead of the graphene anti-corrosion grease of this application, and a matching coating process was used; in Comparative Example 2, single graphene (few-layer graphene) anti-corrosion grease was used instead of the graphene anti-corrosion grease of this application; the DC resistance of the overhead conductors in Comparative Examples 1 and 2 was significantly increased compared to the embodiments, the operating temperature, core wire temperature and interlayer temperature were increased, the line loss of the overhead conductors was higher; and the protection life of the overhead conductors was shorter.
[0133] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0134] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims, and the specification and drawings can be used to interpret the content of the claims.
Claims
1. A corrosion-resistant overhead conductor, characterized in that, Includes aluminum alloy core wire, aluminum monofilament layer, and graphene anti-corrosion grease; The aluminum monofilament layer is stranded on the outside of the aluminum alloy core wire; the graphene anti-corrosion grease is attached to the aluminum alloy core wire and the aluminum monofilament layer, and fills the gap between the aluminum alloy core wire and the aluminum monofilament layer. The graphene anticorrosive grease comprises the following components by mass percentage: 0.5%~3.5% conductive graphene, 0.5%~2.5% thermally conductive graphene, 1%~3% anticorrosive graphene, 0.2%~1.8% lubricating graphene, 0.2%~1.5% nano silver powder, 0.2%~1.5% boron nitride nanosheets, 10%~18% composite lithium-calcium thickener, 1.2%~2.4% additives, and the balance being base oil.
2. The anti-corrosion overhead conductor according to claim 1, characterized in that, The corrosion-resistant overhead conductor meets one or more of the following requirements: (1) The conductive graphene is a few-layer graphene with 3 to 5 layers and the sheet diameter of the few-layer graphene is 2 μm to 5 μm; (2) The thermally conductive graphene is nitrogen-doped graphene, the nitrogen content in the nitrogen-doped graphene is 8%~10% by mass, and the sheet diameter of the nitrogen-doped graphene is 5μm~10μm; (3) The corrosion-resistant graphene is silane coupling agent modified graphene, the density of epoxy groups in the silane coupling agent modified graphene is greater than 0.5 mmol / g, and the sheet diameter of the silane coupling agent modified graphene is 1 μm to 3 μm. (4) The lubricating graphene is oleamide-modified graphene, and the sheet diameter of the oleamide-modified graphene is 0.5μm~2μm.
3. The anti-corrosion overhead conductor according to claim 1, characterized in that, The corrosion-resistant overhead conductor meets one or more of the following requirements: (1) The particle size of the nano silver powder is 30nm~70nm; (2) The diameter of the boron nitride nanosheets is 80 nm to 120 nm; (3) The molar ratio of lithium hydroxide to calcium hydroxide in the raw materials for preparing the composite lithium-calcium thickener is (2~4):1; (4) The base oil includes polyalphaolefin synthetic hydrocarbon PAO6 and modified silicone oil, wherein the mass ratio of polyalphaolefin synthetic hydrocarbon PAO6 to modified silicone oil is (1~2):
1.
4. The anti-corrosion overhead conductor according to claim 1, characterized in that, The additives include one or more of corrosion inhibitors and extreme pressure anti-wear agents; When the additives include corrosion inhibitors, the mass percentage of corrosion inhibitors in the graphene anticorrosive grease is 1% to 1.4%; when the additives include extreme pressure anti-wear agents, the mass percentage of extreme pressure anti-wear agents in the graphene anticorrosive grease is 1% to 1.4%.
5. The anti-corrosion overhead conductor according to any one of claims 1 to 4, characterized in that, The corrosion-resistant overhead conductor meets one or more of the following requirements: (1) The aluminum alloy core wire includes a first aluminum alloy monofilament and multiple second aluminum alloy monofilaments, with the multiple second aluminum alloy monofilaments twisted around the outside of the first aluminum alloy monofilament; (2) The aluminum monofilament layer includes a first aluminum monofilament layer and a second aluminum monofilament layer, wherein the first aluminum monofilament layer is stranded on the outside of the aluminum alloy core wire; and the second aluminum monofilament layer is stranded on the outside of the first aluminum monofilament layer.
6. A method for preparing an anti-corrosion overhead conductor according to any one of claims 1 to 5, characterized in that, Includes the following steps: Graphene anti-corrosion grease is coated onto multiple aluminum monofilaments, and the aluminum monofilaments coated with graphene anti-corrosion grease are twisted together on the outside of an aluminum alloy core wire to form an aluminum monofilament layer.
7. The method for preparing corrosion-resistant overhead conductors according to claim 6, characterized in that, The method for preparing the aluminum alloy core wire includes the following steps: The graphene anti-corrosion grease is coated on the first aluminum alloy monofilament and the second aluminum alloy monofilament; Multiple second aluminum alloy monofilaments are twisted together on the outside of the first aluminum alloy monofilament.
8. The method for preparing corrosion-resistant overhead conductors according to claim 6 or 7, characterized in that, The aluminum monofilament coated with graphene anti-corrosion grease is twisted to the outside of the aluminum alloy core wire, including the following steps: Multiple aluminum monofilaments coated with graphene anti-corrosion grease are twisted together on the outside of the aluminum alloy core wire to form the first aluminum monofilament layer. Multiple aluminum monofilaments coated with graphene anti-corrosion grease are twisted together on the outside of the first aluminum monofilament layer.
9. A production apparatus for producing anti-corrosion overhead conductors according to any one of claims 1 to 5, or a production apparatus used in the preparation method of anti-corrosion overhead conductors according to any one of claims 6 to 8, characterized in that, The device includes a preservative coating apparatus, the preservative coating apparatus comprising: The outer casing has an inner cavity, and the outer casing is provided with a first outer casing oil inlet hole and a second outer casing oil inlet hole communicating with the inner cavity; A coating mold is placed in the inner cavity. The coating mold includes a first half mold and a second half mold. When the first half mold and the second half mold are combined, they form a wire through hole. The first half mold and the second half mold are respectively provided with a first half mold oil inlet hole and a second half mold oil inlet hole. The first half mold oil inlet hole is connected to the first outer shell oil inlet hole, and the second half mold oil inlet hole is connected to the second outer shell oil inlet hole.
10. The production equipment according to claim 9, characterized in that, The anti-corrosion grease coating device further includes a first flow limiting sensor and a second flow limiting sensor, which are respectively disposed on the inner sidewalls of the first housing oil inlet and the second housing oil inlet.